Occurrence and conservation of the Vulnerable titi monkey Callicebus melanochir in fragmented landscapes of the Atlantic Forest hotspot - Costa-Araújo, Rodrigo; Regolin, André Luis [UNESP]; Martello, Felipe; Souza-Alves, João Pedro; Hrbek, Tomas; Ribeiro, Milton Cezar [UNESP] (Cambridge University Press (CUP), 2021)
Tropical forest hotspots have a high diversity of species but have lost > 70% of their original vegetation cover and are characterized by a multitude of small and isolated fragments. Paradoxically, conservation actions in these areas are still mainly focused on protection of large tracts of forests, a strategy now infeasible because of the small area of forest remnants. Here we use the Vulnerable black-handed titi monkey Callicebus melanochir as a model to study the effects of habitat loss, fragmentation and degradation on arboreal mammals and to provide insights for science-driven conservation in fragmented landscapes in tropical forest hotspots. We surveyed 38 Atlantic Forest fragments in Bahia State, Brazil and assessed the effects of patch area, quality and visibility, and landscape connectivity on the occurrence of our model species. Patch area was the single best model explaining species occurrence. Nonetheless, patch quality and visibility, and landscape connectivity, positively affect occurrence. In addition to patch area, patch quality, patch visibility and landscape connectivity are useful for predicting the occurrence of arboreal mammals in the fragments of tropical forest hotspots. We encourage the assessment of habitat quality (based on remotely sensed vegetation indices) and habitat visibility (based on digital elevation models) to improve discoverability of arboreal mammal populations and selection of fragments for conservation purposes across fragmented landscapes of tropical forest hotspots. Large remnants of tropical forest hotspots are scarce and therefore we require baseline data to support conservation actions and management in small forest fragments.
Keywords: Atlantic Forest; Brazil; Callicebus melanochir; degradation; ecological modelling; fragmentation; habitat loss; titi monkey